Presequence protease reverses mitochondria‐specific amyloid‐β‐induced mitophagy to protect mitochondria. Issue 5 (1st April 2023) - Dou, Yunxiao; Tan, Yan
Abstract: Amyloid‐β (Aβ) peptide is accumulated in the mitochondria and has been shown to play a central role in the development of Alzheimer's disease (AD). It has been shown that exposure of neurons to aggregated Aβ can result in damaged mitochondria and dysregulated mitophagy, indicating that changes in the Aβ content of mitochondria may affect the levels of mitophagy and interfere with the progression of AD. However, the direct influence of mitochondrial Aβ on mitophagy has not been elucidated. In the present study, the effect of the mitochondria‐specific Aβ was assessed following a direct change of Aβ content in the mitochondria. We directly change mitochondrial Aβ by transfecting cells with mitochondria‐associated plasmids, including the mitochondrial outer membrane protein translocase 22 (TOMM22) and 40 (TOMM40) or presequence protease (PreP) overexpression plasmids. The changes in the levels of mitophagy were assessed by TEM, Western blot, mito‐Keima construct, organelle tracker, and probe JC‐1 assay. We demonstrated that increased mitochondrial Aβ content enhance mitophagy levels; overexpression of PreP could reverse the mitochondrial Aβ‐induced mitophagy levels in vivo and in vitro by reversing the levels of reactive oxygen species (ROS) and the mitochondrial membrane potential. The data provide novel insight into the role of mitochondria‐specific Aβ in the progression of AD pathophysiology. Abstract : The data confirmed that excess Aβ could damage the mitochondria and increase the activation levels of mitophagy. We further demonstrated that overexpression of PreP could reverse the mitochondrial Aβ‐induced mitophagy levels in vivo and in vitro by reversing the levels of ROS and those of the mitochondrial membrane potential. Therefore, these results may improve the understanding of the relationship between AD and mitophagy and facilitate the development of a novel therapeutic agent for treating mitochondrial Aβ‐mediated diseases.